THE SOUND RANGE AND MICROTONAL CAPABILITIES OF THE TRADITIONAL CHANG INSTRUMENT - Nizomova Mohinur Ulug‘Bek Qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article investigates the sound range and microtonal capabilities of the traditional Uzbek chang. Focusing on the acoustic properties, string configuration, and construction of the instrument, the study examines how the chang produces both standard pitches and microtonal intervals essential for maqom performance. Through spectral analysis, frequency measurement, and performance observation, the research highlights the instrument’s potential for expressive microtonal variation and its role in preserving the nuanced melodic structures of traditional music. The findings provide insights for performers, educators, and instrument makers aiming to optimize tuning, expand expressive potential, and maintain cultural authenticity.